2020
DOI: 10.1001/jama.2020.19334
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Wildfires—A Growing Population Health and Planetary Problem

Abstract: This Viewpoint uses findings from a June 2019 National Academies of Sciences, Engineering, and Medicine (NASEM) workshop report and subsequent data to summarize known environmental and health effects of extreme wildfires, emphasizing their differential adverse effects on low-income, non–English-speaking, and other vulnerable communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Salas et al [ 38 ], Kizer [ 39 ], and Quigley et al [ 40 ] indicated that the problem with evacuation during the COVID-19 pandemic, in combination with a natural hazard, is that these two events call for different preventive strategies. In other words, evacuation is a central strategy for the protection of people from natural hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Salas et al [ 38 ], Kizer [ 39 ], and Quigley et al [ 40 ] indicated that the problem with evacuation during the COVID-19 pandemic, in combination with a natural hazard, is that these two events call for different preventive strategies. In other words, evacuation is a central strategy for the protection of people from natural hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Previous exposure to smoke from wildfires has been linked to increased morbidity from influenza, 75 leading to concern about increased risk of COVID-19 infection associated with wildfires. 76 , 77 , 78 Wildfire smoke contains small particles (PM 2·5 ) that penetrate the lungs, causing irritation and inflammation and conceivably increasing the risk of COVID-19 infection. Individuals most at risk of enhanced susceptibility to respiratory infection due to wildfire smoke exposure are children and infants with small lung size and individuals with pre-existing lung or heart conditions.…”
Section: Coinciding Risks Of Climatic Extremes and Covid-19mentioning
confidence: 99%
“… 30 Smoke from the 2020 California wildfire season also impacted people's lives during the pandemic by necessitating further restrictions on outdoor activities and exacerbating social isolation; with potential mental health implications. 76 …”
Section: Coinciding Risks Of Climatic Extremes and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…1 For example, since the start of 2019, wildfires in California have burned more than 3 million acres, resulting in thousands of destroyed homes and businesses. 2 The wildfires in Australia have affected every state and destroyed more than 2000 homes and burned millions of acres. 3 Wildfires have both direct and indirect effects on health with potentially lasting consequences.…”
Section: Introductionmentioning
confidence: 99%